2021
DOI: 10.3390/w13101376
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Assessment of Future Glacial Lake Outburst Floods in the Poiqu River Basin, Central Himalayas

Abstract: A glacial lake outburst flood (GLOF) is a typical glacier-related hazard in high mountain regions. In recent decades, glacial lakes in the Himalayas have expanded rapidly due to climate warming and glacial retreat. Some of these lakes are unstable, and may suddenly burst under different triggering factors, thus draining large amounts of water and impacting downstream social and economic development. Glacial lakes in the Poiqu River basin, Central Himalayas, have attracted great attention since GLOFs originatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…For example, a 2019 study identified 8 lakes as potentially dangerous 21 ; another 2019 study identified 7 potentially dangerous lakes with transboundary threats along the China-Nepal border 16 ; a 2020 study identified twenty glacial lakes as very highly or highly hazardous 19 . Furthermore, any one of several lakes in the valley, even if they emit a flood at the lowest considered discharge, could cause immense damage in China and across the border into Nepal 24 , as we report in this study.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…For example, a 2019 study identified 8 lakes as potentially dangerous 21 ; another 2019 study identified 7 potentially dangerous lakes with transboundary threats along the China-Nepal border 16 ; a 2020 study identified twenty glacial lakes as very highly or highly hazardous 19 . Furthermore, any one of several lakes in the valley, even if they emit a flood at the lowest considered discharge, could cause immense damage in China and across the border into Nepal 24 , as we report in this study.…”
Section: Introductionmentioning
confidence: 50%
“…We note that geomorphological evidence shows a long history of GLOFs in the Zhangzangbo valley 24 (a part of the Poiqu/Bhotekoshi basin), some of which have caused a severe impact 12 . Taraco Lake, a moraine-dammed lake located in the Tajilingpu valley, had an outburst in August 1935 where livestock and 66,000 m 2 of agricultural fields were destroyed 20 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Every natural phenomenon has its own unique process of formation, occurrence, development, and extinction [15]. For example, floods tend to form quickly and can be formed in a few days or even hours [35]. Hurricanes form relatively faster, probably within hours, minutes, or seconds [36].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, with the gradual increase of glacial melting and the water level of moraine lakes, flood events caused by glacial lake ruptures have occurred frequently in recent years (Liu et al, 2014;Riaz et al, 2014). More and more works have documented the chain disaster events induced by changes in glaciers and glacial lakes (Yang et al, 2011b;Cook et al, 2018;Shangguan et al, 2021;Zhang et al, 2021). Obviously, understanding the response relationship between temperature changes to glaciers and glacial lakes and its impact on glacial debris flow activity will provide some guidance for monitoring and providing early warnings on glacial debris flows and preventing risk in the region.…”
Section: Introductionmentioning
confidence: 99%